2017
DOI: 10.33546/bnj.187
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINANTS OF INDEPENDENT NURSING ACTIONS IN DAILY LIVING ACTIVITIES, CARING & SUPPORT, AND REHABILITATION IN INPATIENT WARDS OF THE GENERAL HOSPITAL OF DR. M. HAULUSSY AMBON

Abstract: Background: Low independent nurse actions leads to poor health care quality. Therefore, understanding the factors affecting independent nursing action is necessity. Objectives: This study aims to analysis the independent nurse actions and its related and predicting factors.Methods: This study used a cross-sectional design with observational technique for data collection. There were 165 nurses recruited using simple random sampling in 14 inpatient wards. Spearman Rank Correlation and multiple regressions were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[22] 2006b Qn Central registration of nurses [23] 2007 Qn Low QNC is related to negative patient satisfaction [24] 2007 Ql Nurses' empowerment [25] 2007 Qn Burnout has a negative impact to QNC [26] 2009 Qn Low QNC is related to low patient satisfaction [27] 2010 Qn QNC has a relationship with patient satisfaction [28] 2010 Qn Nursing care delivery models predicted quality of care [29] 2012 Qn Training will impact QNC [30] 2012 Qn Nursing perception related to documentation [31] 2012 Qn Nursing care delivery models will impact QNC and increase patient satisfaction [32] 2013 Qn Supervision will increase QNC [33] 2013 Qn Workload has a significant relationship with QNC [34] 2013 Qn i) Period of employment; ii) Training; and iii) Workload [35] 2013 Qn Supervision will increase QNC [36] 2015 Qn QNC impacted patient satisfaction [37] 2015 SR i) Healthcare delivery risk infection; ii) Medication errors; iii) Quality care delivery; and iv) The quality of healthcare overall. [38] 2016 Qn Nurse-physician relationship has a relationship with QNC [39] 2016 Qn Critical thinking influences nurse work [40] 2017 Qn Discharge planning influences QNC [41] 2017 Qn Standard will improve QNC [42] 2017 Qn Nursing rounds will improve QNC [43] 2017 Qn i) Knowledge; ii) ability/skills; iii) education; and iv) gender have relationships with nursing action [44] 2018 Qn Job satisfaction will impact QNC [8] 2018 Qn Turnover impacted QNC [45] 2018 Qn QNC impacted patient satisfaction [46] 2018 Qn Training of Soft Skills Caring will increase competency, that would impact patient satisfaction [47] 2018 Ql Competence [48] 2018 LR It helps nurse work effectively and efficiently for increasing quality [49] 2019 Qn Significant relationship [50] 2019 Qn Insufficient nursing activities could not fulfill the patient needs [51] 2019 Qn Primary nursing care delivery mode...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22] 2006b Qn Central registration of nurses [23] 2007 Qn Low QNC is related to negative patient satisfaction [24] 2007 Ql Nurses' empowerment [25] 2007 Qn Burnout has a negative impact to QNC [26] 2009 Qn Low QNC is related to low patient satisfaction [27] 2010 Qn QNC has a relationship with patient satisfaction [28] 2010 Qn Nursing care delivery models predicted quality of care [29] 2012 Qn Training will impact QNC [30] 2012 Qn Nursing perception related to documentation [31] 2012 Qn Nursing care delivery models will impact QNC and increase patient satisfaction [32] 2013 Qn Supervision will increase QNC [33] 2013 Qn Workload has a significant relationship with QNC [34] 2013 Qn i) Period of employment; ii) Training; and iii) Workload [35] 2013 Qn Supervision will increase QNC [36] 2015 Qn QNC impacted patient satisfaction [37] 2015 SR i) Healthcare delivery risk infection; ii) Medication errors; iii) Quality care delivery; and iv) The quality of healthcare overall. [38] 2016 Qn Nurse-physician relationship has a relationship with QNC [39] 2016 Qn Critical thinking influences nurse work [40] 2017 Qn Discharge planning influences QNC [41] 2017 Qn Standard will improve QNC [42] 2017 Qn Nursing rounds will improve QNC [43] 2017 Qn i) Knowledge; ii) ability/skills; iii) education; and iv) gender have relationships with nursing action [44] 2018 Qn Job satisfaction will impact QNC [8] 2018 Qn Turnover impacted QNC [45] 2018 Qn QNC impacted patient satisfaction [46] 2018 Qn Training of Soft Skills Caring will increase competency, that would impact patient satisfaction [47] 2018 Ql Competence [48] 2018 LR It helps nurse work effectively and efficiently for increasing quality [49] 2019 Qn Significant relationship [50] 2019 Qn Insufficient nursing activities could not fulfill the patient needs [51] 2019 Qn Primary nursing care delivery mode...…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the other important factors came from the nurses that were reported from four studies. Those were education [20], [43], gender [43], ability/skills [43], and critical thinking [39]. All of those factors need support from nursing organizations to provide central registration of nurses [21].…”
Section: Factors Related To Quality Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in the last five years, 2016-2020, the actual situation of nursing in Indonesia are common interest or nurse-physician relationship, nursing rounds, nursing documentation, nursing competence, knowledge, ability or skills, gender, training needs, critical thinking, caring behavior, nursing care delivery models, turnover, and managerial function (Anggarawati & Wulan Sari, 2016;Azizah, Widayati, & Rachmania, 2017;Deniati, Anugrahwati, & Suminarti, 2016;Dewanto & Wardhani, 2018;Kusmiran, 2018;Mendrofa & Sagala, 2019;Rahayu, Hartiti, & Rofi'i, 2016;Rohita & Yetti, 2017;Saraswasta & Hariyati, 2018;Sebayang, 2019;Setyowati, Sulisetyawati, & Saelan, 2019;Tuasikal, Margawati, & Dwiantoro, 2017;Yani, Wahyuni, & Priscilla, 2019). Moreover, based on the narrative review related to nursing development in Indonesia found that Indonesia have a complex problem related to quality nursing care and there is limitation study related to factors influencing quality nursing care (Juanamasta, Iblasi, Aungsuroch et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%